A modular platform to develop peptoid-based selective fluorescent metal sensors. Issue 24 (8th March 2017) - Knight, Abigail S.; Kulkarni, Rishikesh U.; Zhou, Effie Y.; Franke, Jenna M.; Miller, Evan W.; Francis, Matthew B.
Abstract : Peptoid ligands were conjugated to fluorescent pyrene yielding a platform for the selective detection of metal ions in complex samples. Abstract : Despite the reduction in industrial use of toxic heavy metals, there remain contaminated natural water sources across the world. Herein we present a modular platform for developing selective sensors for toxic metal ions using N -substituted glycine, or peptoid, oligomers coupled to a fluorophore. As a preliminary evaluation of this strategy, structures based on previously identified metal-binding peptoids were synthesized with terminal pyrene moieties. Both derivatives of this initial design demonstrated a turn-off response in the presence of various metal ions. A colorimetric screen was designed to identify a peptoid ligand that chelates Hg(ii ). Multiple ligands were identified that were able to deplete Hg(ii ) from a solution selectively in the presence of an excess of competing ions. The C-terminal fluoropeptoid derivatives demonstrated similar selectivity to their label-free counterparts. This strategy could be applied to develop sensors for many different metal ions of interest using a variety of fluorophores, leading to a panel of sensors for identifying various water source contaminants.